MOFBOTS: Metal–Organic‐Framework‐Based Biomedical Microrobots. Issue 27 (6th May 2019) - Wang, Xiaopu; Chen, Xiang‐Zhong; Alcântara, Carlos C. J.; Sevim, Semih; Hoop, Marcus; Terzopoulou, Anastasia; de Marco, Carmela; Hu, Chengzhi; de Mello, Andrew J.; Falcaro, Paolo; Furukawa, Shuhei; Nelson, Bradley J.; et al.
Abstract: Motile metal−organic frameworks (MOFs) are potential candidates to serve as small‐scale robotic platforms for applications in environmental remediation, targeted drug delivery, or nanosurgery. Here, magnetic helical microstructures coated with a kind of zinc‐based MOF, zeolitic imidazole framework‐8 (ZIF‐8), with biocompatibility characteristics and pH‐responsive features, are successfully fabricated. Moreover, it is shown that this highly integrated multifunctional device can swim along predesigned tracks under the control of weak rotational magnetic fields. The proposed systems can achieve single‐cell targeting in a cell culture media and a controlled delivery of cargo payloads inside a complex microfluidic channel network. This new approach toward the fabrication of integrated multifunctional systems will open new avenues in soft microrobotics beyond current applications. Abstract : A metal−organic‐framework‐based microrobot that can be precisely navigated by weak rotational magnetic fields is presented. This soft‐based microrobot is capable of performing single‐cell targeting in a cell culture media, as well as a controlled delivery of cargo payloads in a regioselective manner inside a complex microfluidic channel network.